2019
DOI: 10.1136/ijgc-2018-000056
|View full text |Cite|
|
Sign up to set email alerts
|

Location of recurrences in high-risk stage Iendometrial cancer patients not given postoperative radiotherapy: A Danish gynecological cancer group study

Abstract: ObjectivesTo study recurrence rates in Danish high-risk stage I endometrial cancers not given radiotherapy in accordance with the decision of the Danish Gynecological Cancer Group.MethodsThis prospective national cohort study includes all 4707 endometrial carcinomas diagnosed from 2005 to 2012. Of these, 623 patients had grade 3 endometroid adenocarcinoma with >50% myometrial invasion or serous/clear/undifferentiated carcinoma (with any depth of invasion). In 305 patients with high-risk stage I on final pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…In the pioneer study of Alders et al [26] on EBRT for stage I patients, the authors found a decrease in locoregional recurrences, but also a marginal, but non-significant, increase in distant recurrences, which explains the unchanged recurrence-free survival in patients given compared with patients not given radiotherapy. A plausible explanation for this could be that vaginal recurrence occur sooner then distant recurrence [2129], and as many patients experience multiple sites of recurrences, the first recurrences may shift from vaginal to distant if the vaginal recurrence is prevented by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the pioneer study of Alders et al [26] on EBRT for stage I patients, the authors found a decrease in locoregional recurrences, but also a marginal, but non-significant, increase in distant recurrences, which explains the unchanged recurrence-free survival in patients given compared with patients not given radiotherapy. A plausible explanation for this could be that vaginal recurrence occur sooner then distant recurrence [2129], and as many patients experience multiple sites of recurrences, the first recurrences may shift from vaginal to distant if the vaginal recurrence is prevented by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Deaths were retrieved from the Danish Central Person Register and cause of death was checked from the patient's medical records [15]. Histologically-verified recurrences were retrieved from the Danish pathology database, while those not histologically verified were identified from the medical records collected for patients who had died from EC.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Histologically-verified recurrences were retrieved from the Danish pathology database, while those not histologically verified were identified from the medical records collected for patients who had died from EC. Medical records were reviewed to collect time and site of recurrence [15]. As previously described [15], patients underwent abdominal hysterectomy, bilateral salpingo-oophorectomy and intra-abdominal assessment.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second cohort in our study was derived from a Danish population-based study of patients with highrisk EC (6,17) and is described in detail in our companion paper by Peters and colleagues (IJGP21-4497). Cases were collected from the DGCD, a Danish nationwide database that includes nearly all 4707 patients diagnosed with EC from January 1, 2005 to December 31, 2012.…”
Section: The Dgcd Cohortmentioning
confidence: 99%